A balance of capping protein and profilin functions is required to regulate actin polymerization in Drosophila bristle. - Hopmann, R.; Miller, K.G. (Molecular Biology of the Cell, 2003)
Profilin is a well-characterized protein known to be important for regulating actin filament assembly. Relatively few studies have addressed how profilin interacts with other actin-binding proteins in vivo to regulate assembly of complex actin structures. To investigate the function of profilin in the context of a differentiating cell, we have studied an instructive genetic interaction between mutations in profilin (chickadee) and capping protein (cpb). Capping protein is the principal protein in cells that caps actin filament barbed ends. When its function is reduced in the Drosophila bristle, F-actin levels increase and the actin cytoskeleton becomes disorganized, causing abnormal bristle morphology. chickadee mutations suppress the abnormal bristle phenotype and associated abnormalities of the actin cytoskeleton seen in cpb mutants. Furthermore, overexpression of profilin in the bristle mimics many features of the cpb loss-of-function phenotype. The interaction between cpb and chickadee suggests that profilin promotes actin assembly in the bristle and that a balance between capping protein and profilin activities is important for the proper regulation of F-actin levels. Furthermore, this balance of activities affects the association of actin structures with the membrane, suggesting a link between actin filament dynamics and localization of actin structures within the cell.